The effect of artificial selection on phenotypic plasticity in maize - Joseph L. Gage (Nature Portfolio, 2017)
Breeding has increased crop productivity, but whether it has also changed phenotypic plasticity is unclear. Here, the authors find maize genomic regions selected for high productivity show reduced contribution to genotype by environment variation and provide evidence for regulatory control of phenotypic stability.